Statin-associated immune-mediated necrotizing myopathy in Hispanic Americans - Dinh, Tam N.; Nunez, Sharon E.; Gonzales, Kristin M.; Tapia, Krystle L.; Garcia, Eric B.; Fields, Roderick A.; Muruganandam, Maheswari; Emil, N. Suzanne; O’Sullivan, Frank X.; Sibbitt, Wilmer L. (Seminars in arthritis and rheumatism, 2025)
•Pre-existing diabetes mellitus is more common in both Hispanics and Non-Hispanics with idiopathic inflammatory myopathies (IIM) in the Southwestern USA.•Hispanics have markedly increased statin-induced anti-HMGCR antibody immune-mediated necrotizing myopathy (IMNM) compared to Non-Hispanics.•Hispanics have lesser prevalence of cancer-associated idiopathic inflammatory myopathies (IIM) compared to non-Hispanics.•It is uncertain whether these differences result from specific genetic and environmental risk factors, or to greater statin exposure in Hispanics due to increased endemic diabetes mellitus. Idiopathic inflammatory myopathies (IIM) are manifested by proximal muscle weakness, inflammation, and elevation of muscle enzymes. Immune-mediated necrotizing myopathy (IMNM) is a form of IIM often associated with anti-3-hydroxy-3-methylglutaryl coenzyme A reductase (anti-HMGCR) antibodies. Recently, certain regional populations have been found to have increased anti-HMGCR antibody IMNM. The present study compared the epidemiology of IIM and IMNM in the adult Hispanic and non-Hispanic Caucasians in the Southwestern USA. In this retrospective study 97 patients with IIM were self-identified as Hispanic versus non-Hispanic. Statistical comparisons were performed as to prevalence of diabetes mellitus, hyperlipidemia, statin exposure, myopathy diagnosis, muscle histology, autoimmune and myositis-specific autoantibodies, echocardiography, interstitial lung disease, therapy, and outcome. Sixty-two patients self-identified as Hispanic (64 %) and 35 patients as non-Hispanic (36 %). The two groups were similar in terms of baseline characteristics, autoantibody profiles, clinical outcomes, and mortality rates. However, statin-induced anti-HMGCR antibody IMNM was increased in Hispanics (22.6 % versus 5.7 %, OR: 4.81, CI: (1.03, 22.6), p=0.045) as was diabetes mellitus (46.8 % versus 25.7 %, OR: 2.54, CI: (1.02, 6.29), p=0.05). However, there was lesser cancer-associated IIM in Hispanics compared to Non-Hispanics (11.3 % versus 31.4 %, OR: 0.23CI: (0.08, 0.7), p=0.027). Hispanics in the Southwestern USA have increased statin-induced anti-HMGCR antibody IMNM and a lesser prevalence of cancer-associated IIM compared to non-Hispanics. It is uncertain whether these respective differences in statin-induced versus malignancy-associated myositis result from specific genetic and environmental factors, or to greater statin exposure in Hispanics due to increased endemic diabetes mellitus.